A Mini Review on Capillary Isoelectric Focusing-Mass Spectrometry for Top-Down Proteomics - Xu, Tian; Sun, Liangliang (Frontiers in Chemistry, 2021)
Mass spectrometry (MS)-based top-down proteomics (TDP) requires high-resolution separation of proteoforms before electrospray ionization (ESI)-MS and tandem mass spectrometry (MS/MS). Capillary isoelectric focusing (cIEF)-ESI-MS and MS/MS could be an ideal method for TDP because cIEF can enable separation of proteoforms based on their isoelectric points (pIs) with ultra-high resolution. cIEF-ESI-MS has been well-recognized for protein characterization since 1990s. However, the widespread adoption of cIEF-MS for the characterization of proteoforms had been impeded by several technical challenges, including the lack of highly sensitive and robust ESI interface for coupling cIEF to MS, ESI suppression of analytes from ampholytes, and the requirement of manual operations. In this mini review, we summarize the technical improvements of cIEF-ESI-MS for characterizing proteoforms and highlight some recent applications to hydrophobic proteins, urinary albumin variants, charge variants of monoclonal antibodies, and large-scale TDP of complex proteomes.